Human Resources and Logistic Requirements in Problem Based Learning Compared to Traditional Learning - Deo, Satish Kumar (Nepal Orthopaedic Association Journal, 2014)
Problem-based learning (PBL) is a student-centered pedagogy in which students learn about a subject in the context of complex, multifaceted, and realistic problems. Working in groups, students identify what they already know, what they need to know, and how and where to access new information that may lead to resolution of the problem along with discussion of the solution within the group. Few medical schools in Nepal have already incorporated problem-based learning into their curricula and other medical schools are planning to adopt. However, when PBL is introduced into a curriculum, it has implications for staffing and learning resources and demands a different approach to timetabling, workload, and assessment. So, issues like human resources requirements and logistic requirements need to address specifically from Nepal Medical Council for the assurance quality of medical education which, in turn, has contributed in enhancing the quality of health care services in Nepal. Hence, this paper is prepared for developing further understanding about major difference between conventional method of Medical education and PBL in relation to human resources requirements and infrastructure. This article ends with some of the important recommendations that could be considered additionally to existing minimum requirements from Nepal Medical Council for the Medical Schools/ Universities in Nepal who are running or planning to implement Problem-based Learning in their curricula. DOI: http://dx.doi.org/10.3126/noaj.v3i2.9530 NOAJ July-December 2013, Vol 3, Issue 2, 46-47